Enhancing Fire Resistance of Steel Bridge Girders Using External Fire Insulation - Aziz, Esam M. (Kurdistan Journal of Applied Research, 2017)
Fire in steel bridges can be a significant hazard; however, no provisions are specified for fire resistance of bridge structural members in current codes and standards. This paper presents results from numerical analysis on the response of steel bridge girders under fire conditions. A finite element model is developed to evaluate the fire resistance of typical steel girders in bridges using fire insulation with different configurations and thicknesses. The first configuration comprised of applying fire insulation on the web plate of the steel girder, while in the second configuration, the steel section is insulated. Results from numerical analysis indicate that fire resistance and failure mode in steel bridge girders is highly influenced by the insulation configuration and thickness. Applying 25.4mm fire insulation on web plate of steel bridge can increase the fire resistance up to 53 minutes, while applying same insulation thickness on steel section can result in 110 minutes fire resistance.